A Highly Stretchable Supercapacitor Using Laser‐Induced Graphene Electrodes onto Elastomeric Substrate. Issue 10 (10th March 2016) - Lamberti, Andrea; Clerici, Francesca; Fontana, Marco; Scaltrito, Luciano
Abstract : Stretchable electrochemical supercapacitor exploiting laser‐induced graphene (LIG) transfer onto elastomeric substrates is reported. Elastomeric energy‐storage devices are fabricated using polymeric electrolyte and all‐PDMS (all‐polydimethylsiloxane) architecture. The symmetric LIG/PDMS supercapacitor can sustain repeated charge–discharge cycles without suffering significant deterioration of specific capacitance even under stretching and bending conditions.